Analisa Tingkat Bahaya Erosi (Studi Kasus Gang Putingan Jl. Padat Karya Km-2 Muara Rapak Balikpapan Utara) Menggunakan Metode USLE - Hanggara, Ikrar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Erosion is a natural process that often causes problems, especially if erosion has an impact on theurban area. The objective of the present study is to estimate the annual soil loss using USLE model inareas that have hilly topographic conditions in Putingan area, Jl.Padat Karya North Balikpapan Cityof Balikpapan. The method used is USLE (Universal Soil Loss Equation), using Erosivity Factor (R),Erodibility Factor (K), Topographic Factor (LS), Vegetation Cover Factor (C) and Erosion ControlFactor (P) is calculated to obtain the annual rate of erosion that located in Outlet of Watershed. Thequantity of soil loss that obtained from this study are categories as moderate erosion in the amount of130.1 tons / Ha / Year, while for the erosion hazard index included in the High category with aTolerable Soil Loss (TSL) value of 5.42, with that number then It is recommended that immediateaction be taken to reduce the potential for erosion hazard by controlling surface runoff and landengineering so as to reduce the rate of erosion.